Reliability and reproducibility of sciatic nerve magnetization transfer imaging and T2 relaxometry - Preisner, Fabian; Behnisch, Rouven; Fösleitner, Olivia; Schwarz, Daniel; Wehrstein, Michaela; Meredig, Hagen; Friedmann-Bette, Birgit; Heiland, Sabine; Bendszus, Martin; Kronlage, Moritz (European radiology, 2021)
Objectives To assess the interreader and test-retest reliability of magnetization transfer imaging (MTI) and T2 relaxometry in sciatic nerve MR neurography (MRN). Materials and methods In this prospective study, 21 healthy volunteers were examined three times on separate days by a standardized MRN protocol at 3 Tesla, consisting of an MTI sequence, a multi-echo T2 relaxometry sequence, and a highresolution T2-weighted sequence. Magnetization transfer ratio (MTR), T2 relaxation time, and proton spin density (PSD) of the sciatic nerve were assessed by two independent observers, and both interreader and test-retest reliability for all readout parameters were reported by intraclass correlation coefficients (ICCs) and standard error of measurement (SEM). - Results For the sciatic nerve, overall mean ± standard deviation MTR was 26.75 ± 3.5%, T2 was 64.54 ± 8.2 ms, and PSD was 340.93 ± 78.8. ICCs ranged between 0.81 (MTR) and 0.94 (PSD) for interreader reliability and between 0.75 (MTR) and 0.94 (PSD) for test-retest reliability. SEM for interreader reliability was 1.7% for MTR, 2.67 ms for T2, and 21.3 for PSD. SEM for test-retest reliability was 1.7% for MTR, 2.66 ms for T2, and 20.1 for PSD. - Conclusions MTI and T2 relaxometry of the sciatic nerve are reliable and reproducible. The values of measurement imprecision reported here may serve as a guide for correct interpretation of quantitative MRN biomarkers in future studies. Key Points • Magnetization transfer imaging (MTI) and T2 relaxometry of the sciatic nerve are reliable and reproducible. • The imprecision that is unavoidably associated with different scans or different readers can be estimated by the here presented SEM values for the biomarkers T2, PSD, and MTR. • These values may serve as a guide for correct interpretation of quantitative MRN biomarkers in future studies and possible clinical applications.